2015
DOI: 10.1186/s13046-015-0263-1
|View full text |Cite
|
Sign up to set email alerts
|

MTA1-upregulated EpCAM is associated with metastatic behaviors and poor prognosis in lung cancer

Abstract: BackgroundOverexpression of Metastasis-associated protein 1 (MTA1) in various cancer cells promotes tumor invasion and migration and predicts cancer patients’ poor prognosis. The pilot RNA-Seq data from our laboratory indicated that Epithelial cell adhesion molecule (EpCAM) was statistically reduced in MTA1-silencing cells. EpCAM has been recognized as more than a mere cell adhesion molecule and recent findings have revealed its causal role in mediating migratory and invasive capacity. Thus, this study was aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 28 publications
1
29
0
Order By: Relevance
“…Despite recent advances in diagnosis and treatment, the prognosis of lung cancer is still poor [ 3 ]. Therefore, a better understanding of which pathways or proteins are active in lung tumor progression will contribute to the development of early detection and targeted therapy for lung cancer [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite recent advances in diagnosis and treatment, the prognosis of lung cancer is still poor [ 3 ]. Therefore, a better understanding of which pathways or proteins are active in lung tumor progression will contribute to the development of early detection and targeted therapy for lung cancer [ 4 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Originally identified as a novel tumor-specific cell surface antigen following immunization of mice with cancer cells in 1970s ( 1 ), EpCAM has been known to be highly expressed in a variety of epithelial carcinomas ( 104 ). EpCAM is also highly expressed in acute myeloid leukemia (AML), and EpCAM-positive cells may be leukemia stem cells which could promote leukemic progression ( 105 ).…”
Section: Functions Of Epcam In Diseasesmentioning
confidence: 99%
“…EpCAM is a type I transmembrane glycoprotein with an ectodomain, one transmembrane domain, and a cytoplasmic domain of 26 residues 8 , 9 . This glycoprotein is specifically expressed in epithelial tissue and overexpressed in a large variety of human epithelial-derived neoplasms, including cancer of the tongue 10 , thyroid 11 , prostate 12 14 , oesophagus 15 , liver 16 , 17 , colon 18 , breast 19 , 20 , ovary 21 , pancreas 22 , gallbladder 23 , lung 24 , stomach 25 and kidney 26 . Recent studies have revealed that EpCAM is involved in cell signalling, migration, proliferation and differentiation, as well as in metastasis and cancer stem cells 27 .…”
mentioning
confidence: 99%